PENGARUH EKSTRAK ETANOL DAUN MANGROVE Rhizophora stylosa SEBAGAI BIOLARVASIDA TERHADAP PERUBAHAN HISTOLOGI SEL EPITEL MIDGUT LARVA NYAMUK Aedes aegypti - Jumari Ustiawaty; Edy Zacharia (Politeknik Medica Farma Husada Mataram, 2018)
Objective: to determine the potential of ethanol extract of the Rhizophora stylosa mangrove leaves as a biolarvacide by looking at the Lethal Concentration (LC50 and LC90) toxicity and histological changes in the midgut epithelial cells of larvae Aedes aegypti. Research methods: this research is purely experimental use method Posttest-Only Control Group design. The concentration of ethanol extract of Rhizophora stylosa mangrove leaves to be tested is 0 ppm (negative control), 2500 ppm (P1), 3000 ppm (P2), 3500 ppm (P3), 4000 ppm (P4), 4500 ppm (P5), 5000 ppm (P6), and 5500 ppm (P7) and temephos 1 ppm (positive control). The sample used was 20 tail larvae Ae. aegypti instar III. Results of research: this study indicate that the ethanol extract of Rhizophora stylosa mangrove leaves has an activity as a biolarvacide seen from the LC50 of 2885 ppm and LC90 of 4857 ppm. Results of the one way ANOVA test obtained a significance of 0,000, meaning that there is a very significant difference in the amount of mortality of larvae Ae. aegypti instar III due to exposure to Rhizophora stylosa mangrove ethanol extract. The post hoc test (LSD) showed that there were differences in the number of larval deaths at concentrations of 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm, and 5500 ppm. But the concentration of 5000 ppm was not different from the concentration of 5500 ppm. The results of examination of the histological changes of the midgut digestive tract in larvae Ae. aegypti instar III shows that the higher concentration of ethanol extract of Rhizophora stylosa mangrove leaves, the more severe damage that occurs in midgut larvae Ae. aegypti instar III. Spearman Rank test results obtained significance value p = 0,000 <? = 0.05. So it can be concluded that there is a change in the midgut histology of larvae Ae. aegypti instar III shown by the presence of crushing that occurs in the peritrophic membrane, epithelial cells, and basement membrane after exposure to Rhizophora stylosa mangrove leaves extract.